2018
DOI: 10.7592/ejhr2018.6.4.adesoye
|View full text |Cite
|
Sign up to set email alerts
|

Phonological distortion as a humorous strategy in Folarin Falana’s comedy skits

Abstract: Various studies exist on the social functions of humour and such studies have been carried out in diverse fields that range from the humanities to the sciences. In linguistics specifically, research shows that humour has been studied from the perspectives of syntax, pragmatics and semantics; moreover, there is a dearth of studies on the creation of humour through phonological processes. Therefore, this study aims to investigate humour and how it is achieved using phonological processes. The study engages mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Wilkins et al [ 54 ] noted that humor and laughter impart health and well-being. In the Nigerian context, comedy skits are a popular medium of humor, which generates laughter that helps mitigate depression and other stress reactions [ 55 ]. Agwu and Tiemo [ 54 ] reported that laughter and biofeedback are ways to cope with stress among construction personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilkins et al [ 54 ] noted that humor and laughter impart health and well-being. In the Nigerian context, comedy skits are a popular medium of humor, which generates laughter that helps mitigate depression and other stress reactions [ 55 ]. Agwu and Tiemo [ 54 ] reported that laughter and biofeedback are ways to cope with stress among construction personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Agwu and Tiemo [ 54 ] reported that laughter and biofeedback are ways to cope with stress among construction personnel. Comedy is a big business in Nigeria, a menu served at nightclubs in Nigeria and has moved from stand-up to web-based skits [ 55 , 56 ]. This may be because they provide a way to distract Nigerians from the worsening socioeconomic conditions that stare them in the face.…”
Section: Discussionmentioning
confidence: 99%
“…Being a phenomenon that is present in very many cultures, humour has been studied in so many cultural contexts, and its cultural peculiarities are revealed in these different situations. Within the Nigerian context, humour has been studied in situation comedies (Bamgbose & Ehondor 2021;Sunday & Bamgbose 2021), stand-up comedies (Filani 2017;Soneye 2019), computer-mediated communication (Inya 2016), comedy skits (Adesoye 2018), literature (Alabi 2021) and even music (Bamgbose 2019). Its features, functions and strategies have also been explored in detail by several scholars.…”
Section: Reviewmentioning
confidence: 99%
“…In this context, comedy skits are an emerging sub-genre of comedy within digital content creation in Nigeria. It is fast attracting researchers' and even the government's attentionrecently, comedy skit makers were invited to the country's capital, Abuja, by the Nigerian Vice President for a collaboration (Adesoye 2018;API 2021). Specifically, Filani (2017) examined political humour in Nigeria within stand-up comedy.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation